MIGRANTS, MUSLIMS AND REFUGEES IN THE SECULAR AND MULTICULTURAL EUROPE: A PROJECTION TO THE AXIS OF RESPONSIBILITY-INDISPENSABILITY - Hasan Hüseyin Aygül (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Religious and cultural geography of Europe has been changing. Demographicchange that emerged as a result of the recent mobility of refugees and asylumseekers as well as the long settled migrant groups cause anxiety. Especially,as the existence of Islam, which has been coded as the “other” for hundreds ofyears, is established and as the encounters with the Muslim “subject” in thesecular public space increase, there occur some conflicts, ruptures andtransformations.In European public opinion Islam is seen as afundamentalist religion, so is claimed that it does not fit to secularism,modernity or democracy. There are various discussions on the possibility ofarticulating Islam within a secularism that already regards Christianity, aswell as of multiculturalism or living together. This study will discuss the possibilityor impossibility of living together or a multicultural social model, takinginto consideration some cases of rising racism, xenophobia, Islamophobia andstatistical data considering ghettoization and the rates of unemployment andcrime